The question of patriotism in the thought of Sheikh Mohamed Al Bachir Al Ibrahimi - ben hamed, saadia (Journal of Social Sciences and Humanities, 2021)
Mohamed Al Bachir Al Ibrahimi is considered to be one of the most famous scientists and pioneers in Algeria, by who the country kept its language and relegion preserved against the different waves of the colonialism distortion . He defended the Isalmicrelegion , Arabic identity and traditions of the country , saying no to any kinds of naturalization and integration. Mohamed Al Bachir Al Ibrahimi quoted " Algeria is not French and can not be Frenshized , these are words said by our anestors and will kept said by the next generations ". Undoubtly that the immense faith and sincerity of the fight of Seikh Al Ibrahimi played a key role for him to stand like a mountain against the colonizer , when he kept fighting tirelessly with the goal of freeing the country . He helped in spreading the advice , patriotism and assistance among the young people and raising their level of awareness by building schools , mosques and organizations ..etc and giving birth to press and media movements . All These efforts culminated in the make of a bright and well educated Algerian generation that was the backbone of the Algerian revival against the colonizer.